Increased Variation in Body Weight and Food Intake Is Related to Increased Dietary Fat but Not Increased Carbohydrate or Protein in Mice - Wu, Yingga; Hu, Sumei; Yang, Dengbao; Li, Li; Li, Baoguo; Wang, Lu; Li, Min; Wang, Guanlin; Li, Jianbo; Xu, Yanchao; Zhang, Xueying; Niu, Chaoqun; et al. (Frontiers in Nutrition, 2022)
A variety of inbred mouse strains have been used for research into metabolic disorders. Despite bring inbred they display large inter-individual variability for many traits like food intake and body weight. However, the relationship between dietary macronutrients and inter-individual variation in body weight and food intake of different mouse strains is still unclear. We investigated the association between macronutrient content of the diet and variations in food intake, body composition and glucose tolerance by exposing five different mouse strains (C57BL/6, BALB/c, C3H, DBA/2, FVB) to 24 different diets with variable protein, fat and carbohydrate content. We found only increasing dietary fat, but not protein or carbohydrate had a significant association (positive) with variation of both food intake and body weight. The highest variations of both body weight and food intake occurred with 50% dietary fat. However, there were no significant relationships between the variation in fat and lean mass with dietary protein, fat or carbohydrate levels. Also none of the dietary macronutrients had significant impacts on the variation of glucose tolerance ability in C57BL/6 mice. In conclusion, the variations in food intake and body weight changes increased with the elevation of dietary fat level.